2009
DOI: 10.1017/s136898000800325x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary consumption of phytochemicals and breast cancer risk in Mexican women

Abstract: Objective: To perform an evaluation of selected phytochemicals intake and breast cancer (BC) risk in Mexican women. Design: We conducted hospital-based case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
1
28
0
3
Order By: Relevance
“…In the present study, the dose-dependent effect of PIN on breast cancer cells was not measured; therefore, it is possible that at higher concentrations this compound may also inhibit the growth of MCF-7 cells. Further studies will be necessary to clarify these points and will be of particular importance considering that a recent case-control study showed a clear and strong inverse correlation (OR = 0.19; 95% CI: 0.06, 0.62; P for trend = 0.006) between the consumption of PIN and breast cancer risk in premenopausal women (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the dose-dependent effect of PIN on breast cancer cells was not measured; therefore, it is possible that at higher concentrations this compound may also inhibit the growth of MCF-7 cells. Further studies will be necessary to clarify these points and will be of particular importance considering that a recent case-control study showed a clear and strong inverse correlation (OR = 0.19; 95% CI: 0.06, 0.62; P for trend = 0.006) between the consumption of PIN and breast cancer risk in premenopausal women (36).…”
Section: Discussionmentioning
confidence: 99%
“…FFQs that were used varied in length, ranging from 67 to 208 items. Only one study validated its FFQ specifically for plant lignan assessment (Torres-Sanchez et al, 2008), although a UK study used the combination of an FFQ and 24-h recalls to group participants into quartiles of intake (dos Santos Silva et al, 2004). In addition, the possibility of residual confounding cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Los países con mayor número de estudios publicados son Uruguay [7][8][9]11,12,14,17,18 y México 10,13,[19][20][21][22][23]30 (33 y 30% de las publicaciones, respectivamente) (cuadro I). En Uruguay, los estudios se han enfocado sobre todo en el consumo de carnes y sus métodos de preparación.…”
Section: Resultsunclassified
“…La investigación sobre dieta y CM conducida en diferentes países de Latinoamérica ha contribuido al estado del arte y muestra en particular el efecto protector de los vegetales y frutas, 5,9 el pescado, 12 la fibra, 17 la vitamina B 12 y el folato, 21 varios fitoestrógenos (en particular el flaván 3-ol y el pinoresinol), 23 el licopeno 9 y las grasas poliinsaturadas, 18,19 además del incremento del riesgo potencial de la elevada ingestión calórica, 5 el consumo de carnes rojas, 7,8,15,16 carnes procesadas, 14 la forma de preparación de las carnes, 12 leche y algunos productos lácteos, 11 grasas saturadas 7 y sacarosa, 20 además de compuestos secundarios como las aminas heterocíclicas. 8 No obstante, es importante mencionar que pese al gran número de proyectos realizados, un gran porcentaje de ellos carece de las características metodológicas que sustente con rigor científico los resultados.…”
Section: Discussionunclassified
See 1 more Smart Citation